Impact of UV- and carbodiimide-based crosslinking on the integrin-binding properties of collagen-based materials. (December 2019) - Bax, Daniel V.; Davidenko, Natalia; Hamaia, Samir W.; Farndale, Richard W.; Best, Serena M.; Cameron, Ruth E.
Abstract: Collagen constructs are widely used for tissue engineering. These are frequently chemically crosslinked, using EDC, to improve their stability and tailor their physical properties. Although generally biocompatible, chemical crosslinking can modify crucial amino acid side chains, such as glutamic acid, that are involved in integrin-mediated cell adhesion. Instead UV crosslinking modifies aromatic side chains. Here we elucidate the impact that EDC, in combination with UV, exerts on the activity of integrin-binding motifs. By employing a model cell line that exclusively utilises integrin α2 β1, we found that whilst EDC crosslinking modulated cell binding, from cation-dependent to cation-independent, UV-mediated crosslinking preserved native-like cell binding, proliferation and surface colonisation. Similar results were observed using a purified recombinant I-domain from integrin α1 . Conversely, binding of the I-domain from integrin α2 was sensitive to UV, particularly at low EDC concentrations. Therefore, from this in vitro study, it appears that UV can be used to augment EDC whist retaining a specific subset of integrin-binding motifs in the native collagen molecule. These findings, delineating the EDC- and UV-susceptibility of cell-binding motifs, permit controlled cell adhesion to collagen-based materials through specific integrin ligation in vitro . However, in vivo, further consideration of the potential response to UV wavelength and dose is required in the light of literature reports that UV initiated collagen scission may lead to an adverse inflammatory response. Statement of significance: Recently, there has been rapid growth in the use of extracellular matrix-derived molecules, and in particular collagen, to fabricate biomaterials that replicate the cellular micro-environment. Often chemical or physical crosslinkers are required to enhance the biophysical properties of these materials. Despite extensive use of these crosslinkers, the cell-biological consequences have not been ascertained. To address this, we have investigated the integrin-binding properties of collagen after chemically crosslinking with EDC and physically crosslinking with UV-irradiation. We have established that whilst EDC crosslinking abates all of the integrin binding sites in collagen, UV selectively inhibits interaction with integrin-α2 but not -α1 . By providing a mechanistic model for this behaviour, we have, for the first time, defined a series of crosslinking parameters to systematically control the interaction of collagen-based materials with defined cellular receptors. Graphical abstract: Image, graphical abstract